(untitled) (Nigerian Journal of Technology, 2020)
This study evaluate the use of Disposable Food Pack (DFP) as a modifier for bitumen for an improved Hot Mix Asphalt (HMA). The bitumen was modified with 2%, 4%, 6%, 8% and 10% DFP obtained from domestic waste. The penetration, ductility and specific gravity of DFP modified bitumen decreased from 68mm to 59.5mm, 110cm to 101cm and 1.025 to 1.012 respectively with increase in DFP, while softening point increased from 49.5oC to 54.5oC with increase in DFP. The Marshal Stability results revealed that the DFP modified bitumen increased the stability values of the compacted mixes to a maximum of 9.33kN at 8% DFP content. The flow showed decrease from 3.18mm at 2% DFP to 2.94mm at 10% DFP, whereas the density of the compacted mixes increased to a maximum of 2.293g/cm3 with increased modifier. An Optimum DFP Content of 6.7% by weight of the Optimum Bitumen Content (OBC) is recommended. http://dx.doi.org/10.4314/njt.v39i4.7